PP15. MICRORNA REGULATION OF INTRA-TUMOUR METABOLIC HETEROGENEITY IN GLIOBLASTOMA MULTIFORME - Alfardus, Ms Huda (Neuro Oncol, 2017)
Glioblastoma multiforme (GBM) is the most aggressive and common malignant brain and central nervous system tumour. GBM adaptation to the diverse micro-environmental conditions, including varying degree of vasculature, nutritional supply, oxygen and pH levels, is reflected on its temporo-spatial genetic and metabolic heterogeneity. microRNA (miRNA) are a class of short non-protein coding sequences that exert post-transcriptional controls on gene expression, have been shown to regulate metabolism-associated genes in GBM. However intratumour heterogeneity of miRNA expression profiles has not been examined in a similar fashion to studies conducted on gene expression (mRNA profiling). This study aims to comprehensively characterise the spatial variability in miRNA expression profile within GBM within different micro-environmental niches. We will relate this to data regarding metabolic profiles in GBM cell cultures, including primary in house lines derived from the invasive edge of tumours. In our study, we use genome-wide miRNA expression profiling to assess the heterogeneity in miRNA expression levels between distinct regions within GBM tumours. Total RNA extracted from surgical specimens (n=72) sampled from core, proliferative rim, invasive margins and patient-derived cell lines are analysed using the human miRNA v4.1 Array Plate and Gene Titan® Scanner (Affymetrix).Gene targets for analysis are selected with miRNA target gene prediction software (MiRBase), and protein levels are validated through immunohistochemistry and Western blotting. The initial results from the analysis will be discussed. Metabolic analysis using lactate assays (Sigma-Aldrich) showed that patient-derived cell lines from the invasive edge of GBM tumours produced significantly (P< 0.001) more lactate than established GBM cell lines originally derived from the tumour core. This could reflect the heterogeneity in metabolic adaptation to the tumour micro-environment and cellular phenotypes from which the different cell lines were derived. The effect of the resultant highly acidic micro-environment created by the patient-derived GBM cells on their migration potential was assessed using the wound healing scratch assay and the differences in response investigated further using quantitative RT-PCR to identify differences in Epithelial to Mesenchymal Transition (EMT) markers. Understanding the intratumour heterogeneity in miRNA expression will add an extra layer of complexity to the regulation of metabolic heterogeneity in GBM. The set of the differentially expressed miRNA in different regions of the GBM tumour can serve as therapeutic targets to selectively disrupt and destabilise dysregulated metabolic processes in GBM cells across a widespread area of the brain, whilst sparing normal brain cells that employ functional metabolic pathways.